1979
DOI: 10.1080/03015521.1979.10426155
|View full text |Cite
|
Sign up to set email alerts
|

V. Unimproved North Island hill country, “Ballantrae”

Abstract: N fixation was measured at 15 sites on an area of poorly developed, hill-country pasture at the DSIR Grasslands Division hill-country research property, in the southern Ruahine Range. The average total of N fixed in one year was estimated to be 34 kglha, about half of which was attributed to non-symbiotic, freeliving micro-organisms. The relationships between N fixation, seasonal climatic variables, differences in growth patterns of legume species, and total legume dry matter production are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The simple regression models for these relationships are (A) LPROD = 1.78 P + 718, r2 = 0.55, p < 0.001; and (B) %LPROD = 0.00012 P + 0.095, r* = 0.35, p = 0.033. changes in the N:P supply ratios also should have significant effects on measured rates of legume N-fixation (NFIX, kg N ha-' yr-'). This hypothesis was tested directly using measurements of nitrogen fixation and soil chemistry pooled from experimental studies of New Zealand pastures (Sears et al 1965;Ledgard et al 1987;Hogland and Brock 1978;Grant and Lambert 1979;Hoglund et al 1979;Crush et al 1982Crush et al , 1983. Prior to multiple regression analysis (Wilkinson 1998) the nitrogen fixation and soil nitrogen data were transformed to their common logarithms.…”
Section: Effects Of N:p Ratios On Rates Of Symbiotic N-fixationmentioning
confidence: 99%
“…The simple regression models for these relationships are (A) LPROD = 1.78 P + 718, r2 = 0.55, p < 0.001; and (B) %LPROD = 0.00012 P + 0.095, r* = 0.35, p = 0.033. changes in the N:P supply ratios also should have significant effects on measured rates of legume N-fixation (NFIX, kg N ha-' yr-'). This hypothesis was tested directly using measurements of nitrogen fixation and soil chemistry pooled from experimental studies of New Zealand pastures (Sears et al 1965;Ledgard et al 1987;Hogland and Brock 1978;Grant and Lambert 1979;Hoglund et al 1979;Crush et al 1982Crush et al , 1983. Prior to multiple regression analysis (Wilkinson 1998) the nitrogen fixation and soil nitrogen data were transformed to their common logarithms.…”
Section: Effects Of N:p Ratios On Rates Of Symbiotic N-fixationmentioning
confidence: 99%
“…It produces 70% of its annual herbage accumulation in the spring (Lambert et al unpublished data), is adapted to low P availability and summer drought conditions (Brock 1973), and can fix substantial amounts of N in hill pastures (Grant & Lambert 1979).…”
Section: Suckling Cjovermentioning
confidence: 99%
“…Non symbiotic N fixation. Grant & Lambert (1979) suggested that in a poorly developed hill country pasture, N fixation by nonsymbiotic organisms and atmospheric deposition can be, together, as important as clover N fixation. They estimated that approximately 21 kg N ha…”
Section: Introductionmentioning
confidence: 99%